Socialization of Product Rebranding to Improve Understanding Among MSME Actors in Gebang Putih Village - Dwi Syerli Inda Rahmawati; Gideon Setyo Budiwitjaksono; Fiorara Gustie; Noviyanti Pusvita; Aulia Friya Rahana Dewi; Rio Alghaniy Putra (Unram Journal of Community Service, 2025)
Rebranding is a crucial strategy for Micro, Small, and Medium Enterprises (MSMEs) to strengthen product identity and make it more relevant to modern market demands. However, many MSME actors still lack a comprehensive understanding of rebranding concepts and benefits, particularly in terms of visual identity, brand communication, and digital marketing utilization. This community service activity aimed to improve MSME players' understanding in Gebang Putih Subdistrict through a socialization program conducted by students of the KKNT Bela Negara SDGs team from Universitas Pembangunan Nasional Veteran Jawa Timur. The method consisted of three main stages: observation, interactive socialization, and evaluation. The results showed that the socialization was effective in raising awareness and motivation among MSME actors regarding the importance of rebranding. Several business owners began implementing changes in their marketing strategies, such as using social media, strengthening visual branding, and applying product storytelling. However, the implementation still faced technical limitations and resource constraints. Thus, the socialization served as an essential initial step, but requires follow-up training and support to ensure sustainable and optimal rebranding practices.